Towards Better Understanding of Pea Seed Dormancy Using Laser Desorption/Ionization Mass Spectrometry - Cechová, Monika; Válková, Markéta; Hradilová, Iveta; Janská, Anna; Soukup, Aleš; Smýkal, Petr; Bednář, Petr (International journal of molecular sciences, 2017)
Seed coats of six pea genotypes contrasting in dormancy were studied by laser desorption/ionization mass spectrometry (LDI-MS). Multivariate statistical analysis discriminated dormant and non-dormant seeds in mature dry state. Separation between dormant and non-dormant types was observed despite important markers of particular dormant genotypes differ from each other. Normalized signals of long-chain hydroxylated fatty acids (HLFA) in dormant JI64 genotype seed coats were significantly higher than in other genotypes. These compounds seem to be important markers likely influencing JI64 seed imbibition and germination. HLFA importance was supported by study of recombinant inbred lines (JI64xJI92) contrasting in dormancy but similar in other seed properties. Furthemore HLFA distribution in seed coat was studied by mass spectrometry imaging. HLFA contents in strophiole and hilum are significantly lower compared to other parts indicating their role in water uptake. Results from LDI-MS experiments are useful in understanding (physical) dormancy (first phases of germination) mechanism and properties related to food processing technologies (e.g., seed treatment by cooking).
Keywords: laser desorption-ionization mass spectrometry; semena rostlinná; pea; Fatty Acids; mastné kyseliny; fatty acid; seed coat; vegetační klid; Seeds; Plant Dormancy; multivariate statistics; Mass Spectrometry; imaging mass spectrometry; Pisum sativum; hmotnostní spektrometrie; seed hardness; seed dormancy; hrách setý